Melatonin Enhances the Usefulness of Ionizing Radiation: Involving the Regulation of Different Steps of the Angiogenic Process - González-González, Alicia; González, Alicia; Rueda, Noemí; Alonso-González, Carolina; Menéndez-Menéndez, Javier; Gómez-Arozamena, José; Martínez-Campa, Carlos; Cos, Samuel (Frontiers in Physiology, 2019)
Radiotherapy is a part of cancer treatment. To improve its efficacy has been combined with radiosensitizers such as antiangiogenic agents. Among the mechanisms of the antitumor action of melatonin are antiangiogenic effects. Our goal was to investigate whether melatonin may modulate the sensitivity of endothelial cells (HUVECs) to ionizing radiation. Melatonin (1 mM) enhanced the inhibition induced by radiation on different steps of the angiogenic process, cell proliferation, migration and tubular network formation. In relation with the activity and expression of enzymes implicated in estrogen synthesis, in cocultures HUVECs/MCF-7, radiation downregulated aromatase mRNA expression, aromatase endothelial-specific promoter I.7, sulfatase activity and expression and 17β-HSD1 activity and expression and melatonin enhanced these effects. Radiation and melatonin induced a significant decrease in VEGF, ANG-1 and ANG-2 mRNA expression. In ANG-2 and VEGF mRNA expression melatonin potentiated the inhibitory effect induced by radiation. In addition, melatonin counteracted the stimulatory effect of radiation on FGFR3, TGFα, JAG1, IGF-1 and KDR mRNA expression and reduced ANPEP expression. In relation with extracellular matrix molecules, radiation increased MMP14 mRNA expression and melatonin counteracted the stimulatory effect of radiation on MMP14 mRNA expression and increased TIMP1 expression, an angiogenesis inhibitor. Melatonin also counteracted the stimulatory effect of radiation on CXCL6, CCL2, ERK1, ERK2 and AKT1 mRNA expression and increased the inhibitory effect of radiation on NOS3 expression. In CAM assay, melatonin enhanced the reduction of the vascular area induced by radiation. Melatonin potentiated the inhibitory effect on the activation of p-AKT and p-ERK exerted by radiation. Antiangiogenic effect of melatonin could be mediated through AKT and ERK pathways, proteins involved in vascular endothelial cell growth, cell proliferation, survival, migration and angiogenesis. In addition, radiation increased endothelial cell permeability and melatonin counteracted it by regulating the internalization of VE-cadherin. Radiation has some side effects on angiogenesis that may reduce its effectiveness against tumor growth and melatonin is able to neutralize these negative actions of radiation. Additionally, melatonin potentiated radiation-induced antiangiogenic actions on several steps of the angiogenic process and enhanced its antitumor action. Our findings point to melatonin as a useful molecule as adjuvant to radiotherapy in cancer treatment.